2020
DOI: 10.1177/0194599820973644
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Parental Intolerance of Uncertainty and Decisional Conflict in Pediatric Otolaryngologic Surgery

Abstract: Objective To assess the relationship between depression, anxiety, stress, worry, intolerance of uncertainty (IU), and shared decision making (SDM) in parents of pediatric otolaryngology surgical patients with their perceptions of decisional conflict (DC). Study Design Cross-sectional. Setting Academic pediatric otolaryngology outpatient clinic. Methods Participants were legal guardians of pediatric patients who met criteria for otolaryngologic surgery. Participants completed a demographic survey as well as val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A previous study in parents of pediatric otolaryngology patients suggested that there is a negative relationship between decisional conflict and IU, such that as IU increases DC will decrease. 28 IU may be an important predictor of decisionmaking difficulty and parental dissatisfaction in this group. It is important to note that IU is a modifiable psychologic construct.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study in parents of pediatric otolaryngology patients suggested that there is a negative relationship between decisional conflict and IU, such that as IU increases DC will decrease. 28 IU may be an important predictor of decisionmaking difficulty and parental dissatisfaction in this group. It is important to note that IU is a modifiable psychologic construct.…”
Section: Discussionmentioning
confidence: 93%
“…In real life, health-related treatment decisions can be confusing and stressful, and there is evidence that patients and people making decisions for others, especially parents, experience difficulty making treatment-related medical decisions. [2][3][4][5][6][7][8] This decisional conflict is defined as the state of uncertainty people experience when deliberating which course of action to take when making treatment-related medical decisions. 9…”
Section: Introductionmentioning
confidence: 99%